Summarization by Domain Ontology Navigation. Issue 1 (29th November 2012) - Andreasen, Troels; Bulskov, Henrik; Reformat, Marek Z.
<x xml:space="preserve">Abstract</x> A summary is a concise description that reflects the essence of a subject. A text, a collection of text documents, or a query answer can be summarized by simple means such as an automatically generated list of the most frequent words or "advanced" by a meaningful natural language description of the subject. In between these two extremes, conceptual summaries encompass selected concepts derived using background knowledge. We address in this paper an approach where conceptual summaries are provided through a conceptualization as given by an ontology. The ontology guiding the summarization can be a simple taxonomy or a generative domain ontology. A domain ontology can be provided by a preanalysis of a domain corpus and can be used to condense improved summaries that better reflects the conceptualization of a given domain.